ANALISIS PERBAIKAN TATA LETAK FASILITAS PADA GUDANG BAHAN BAKU DAN BARANG JADI DENGAN METODE SHARE STORAGE DI PT . BITRATEX INDUSTRIES SEMARANG - Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2012)
Warehouse layout is how to set up industrial facilities to support the smooth production process. Good warehouse layout is essential that the role of a activity inside the process to run smoothly. In order warehouse layout planning includes planning and organizing warehouse layout, equipment, material flow and the people who work at each work station. If prepared properly, then the work operations to be more effective and efficient. Conditions warehouse layout are unfounded a comprehensive layout design can lead to inefficiencies that led to the time period of the material in the material handling by the operator due to time constraints. Share storage method is the method used to set the storage to be more effective. The frequency shift of fast-moving material is stored in a warehouse that is closer to the process and the frequency shift slow-moving material is stored in a warehouse away from the process. Based on data obtained from the research at PT. Bitratex Industries Semarang for designing warehouse layout assembling parts with shared storage method and the results obtained within a more efficient switching time is 40.74 m. Keywords: layout, share storage